2020
DOI: 10.1038/s41416-020-1015-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated clinico-molecular profiling of appendiceal adenocarcinoma reveals a unique grade-driven entity distinct from colorectal cancer

Abstract: Background Appendiceal adenocarcinoma (AA) is an orphan disease with unique clinical attributes but often treated as colorectal cancer (CRC). Understanding key molecular differences between AA and CRC is critical. Methods We performed retrospective analyses of AA patients (N = 266) with tumour and/or blood next-generation sequencing (NGS) (2013–2018) with in-depth clinicopathological annotation. Overall survival (OS) was examined. For comparison, CRC cohorts annotated for sidedness, consensus molecular subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 47 publications
2
46
1
Order By: Relevance
“…61 Most patients with signet ring cell tumors develop metastatic disease, all with peritoneal disease and only 10% occurring at distant sites. 62 Although AAs have a lower rate of KRAS and GNAS mutations (56% and 25%, respectively) compared with appendiceal MAN, 11,63,64 the rates are still higher than those seen in colorectal cancer. Mutation rates in TP53 (23%), APC (2%), and PIK3CA (2%) are also lower than those seen in colorectal cancer.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…61 Most patients with signet ring cell tumors develop metastatic disease, all with peritoneal disease and only 10% occurring at distant sites. 62 Although AAs have a lower rate of KRAS and GNAS mutations (56% and 25%, respectively) compared with appendiceal MAN, 11,63,64 the rates are still higher than those seen in colorectal cancer. Mutation rates in TP53 (23%), APC (2%), and PIK3CA (2%) are also lower than those seen in colorectal cancer.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…Similarly, Raghav et al published TP53 mutations were enriched in moderately-differentiated and poorly-differentiated mucinous adenocarcinomas, and TP53 mutational status correlated with poor patient OS after CRS-HIPEC. 33 However, mutations in TP53 were not an independent prognostic factor of OS when adjusted for AJCC/WHO grade. The authors therefore hypothesized that disseminated AMNs represents a network-based disease, arising not from a single dominant gene, but rather through dysregulation of multiple genomic pathways that converge to a speci c oncologic state.…”
Section: Discussionmentioning
confidence: 92%
“…Despite these unique clinical attributes, appendiceal neoplasms and colorectal carcinomas have been managed similarly due to their relative anatomic proximity and shared embryological origin. However, recent molecular profiling analyses using next-generation sequencing (NSG) have shown that appendiceal neoplasms have distinct molecular profiles and genetic mutations [6]. One study revealed high rates of KRAS and GNAS (28% vs 2%) mutations in appendiceal carcinoma compared to CRC [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent molecular profiling analyses using next-generation sequencing (NSG) have shown that appendiceal neoplasms have distinct molecular profiles and genetic mutations [6]. One study revealed high rates of KRAS and GNAS (28% vs 2%) mutations in appendiceal carcinoma compared to CRC [6,7]. Appendiceal carcinoma was also associated with fewer APC (9% vs 55%) and TP53 (27 vs 67%) mutations compared to CRC 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation